Initial oral biofilm formation on titanium implants with different surface treatments: An in vivo study - Ferreira Ribeiro, Cyntia; Cogo-Müller, Karina; Franco, Gilson Cesar; Silva-Concílio, Laís Regiane; Sampaio Campos, Márcia; De Mello Rode, Sigmar [UNESP]; Claro Neves, Ana Christina (Elsevier, 2016)
Objective The aim of this study was to examine in vivo the initial bacterial adhesion on titanium implants with different surface treatments. Design Ten subjects wore oral splints containing machined pure titanium disks (Ti-M), acid-etched titanium (Ti-AE) and anodized and laser irradiated disks (Ti-AL) for 24 h. After this period, disks were removed from the splints and adherent bacteria were quantified by an enzymatic assay to assess total viable bacteria and by Real Time PCR to evaluate total bacteria and Streptococcus oralis levels. Additionally, the initial adherent microorganisms were visualized by scanning electron microscopy (SEM). Titanium surface morphology was verified using SEM, and roughness was evaluated by profilometer analysis. Results Regarding titanium surface roughness, Ti-AL (1.423 ± 0.397) showed significantly higher Ra values than did Ti-M (0.771 ± 0.182) and Ti-AE (0.735 ± 0.196) (p < 0.05, ANOVA - Tahame). Ti-AE and Ti-AL presented roughened micro-structure surfaces characterized by open pores, whereas Ti-M showed long grooves alternating with planed areas. Comparing the Ti-M, Ti-AE and Ti-AL groups for viable bacteria (MTT assay), total bacteria and S. oralis quantification (qPCR), no significant differences were observed among these three groups (p > 0.05, ANOVA - Tahame). SEM images showed similar bacterial adhesion on the three titanium surfaces, predominantly characterized by cocci and several bacilli, indicating an initial colonization of the oral biofilm. Conclusion In conclusion, roughness and microtopography did not stimulate initial biofilm formation on titanium surfaces with different surface treatments.
Keywords: Biofilm; Implants; Streptococcus oralis; Surface properties; Titanium